Randomised controlled trial of the use of drains versus no drains after burr hole evacuation of chronic subdural haematoma - Santarius, T.; Ganesan, D.; Kirkpatrick, P.J.; Chia, H.L.; Jalloh, I.; Peter, S.; Richards, H.K.; Marcus, H.; Parker, R.A.; Price, S.J.; Kirollos, R.W.; Hutchinson, P.J. (2009)
Chronic subdural hematoma (CSDH) is a cause of significant morbidity and mortality which is often amenable to surgical drainage. The majority of patients recover rapidly after surgical intervention, but 5% to 30% experience recurrence. Although the use of drains after burr hole evacuation may lower recurrence, they are not used routinely because of a lack of evidence showing efficacy and a concern for increasing surgical morbidity. The aim of this study was to investigate the use of drains in reducing recurrence rates, and their influence on clinical outcome for those presenting with a CSDH.